Enhancing the comprehension of mixed layer depth control on the Mediterranean phytoplankton phenology. Issue 7 (15th July 2013) - Lavigne, Héloïse; D'Ortenzio, Fabrizio; Migon, Christophe; Claustre, Hervé; Testor, Pierre; d'Alcalà, Maurizio Ribera; Lavezza, Rosario; Houpert, Loïc; Prieur, Louis
Abstract : [1] Phytoplankton phenology is primarily affected by physical forcing. However, its quantification is far from being completely understood. Among the physical forcing factors, the mixed layer depth (MLD) is considered to have the strongest impact on phytoplankton dynamics, and consequently, on their phenology. The role of MLD variations in shaping the phytoplankton phenology was explored in the Mediterranean Sea, a basin displaying contrasting phenological regimes. A database of MLD estimations was merged with ocean color chlorophyll concentrations ([Chl]SAT ) to generate concomitant annual MLD and [Chl]SAT cycles. Several indices were calculated to quantitatively analyze these cycles. The relevance of indices summarizing the temporal difference between main characteristics of MLD and [Chl]SAT cycles was emphasized. As previously observed, two dominant phenological regimes coexist in the Mediterranean Sea. The first is marked by a typical spring bloom, as in temperate regions. The second displays a low seasonality and an absence of an intense [Chl]SAT peak as in subtropical areas. The MLD is shown to play a key role in determining the dominant phenological regime in a given area. Results also show that regions having low seasonality display concomitant MLD and [Chl]SAT maxima, whereas [Chl]SAT peaks are generally observed 30 days after MLD peaks in regions with strongest seasonality. Over the whole basin, [Chl]SAT increase starts 1 month after the initiation of MLD deepening. Finally, after examining the impact of MLD on light and nutrient availability for phytoplankton, mechanisms were proposed to explain the time lags between MLD and [Chl]SAT increase and MLD and [Chl]SAT maxima. Key Points: Role of the mixed layer depth on phytoplankton phenology in the Mediterranean Study of the match/mismatch between mixed layer depth and chlorophyll events Multi‐scale and bioregionalization‐driven analysis of in situ and satellite data